Perceived barriers and facilitators to physical activity in childhood cancer survivors and their parents: A large‐scale interview study from the International PACCS Study. Issue 1 (17th October 2022) - Larsen, Elna Hamilton; Mellblom, Anneli Viktoria; Larsen, Marie Hamilton; Ruud, Ellen; Thorsen, Lene; Petersen, Natasha Nybro; Larsen, Hanne Bækgaard; Fridh, Martin Kaj; Lie, Hanne Cathrine
Abstract: Background: Physical activity (PA) may reduce risks of late effects in childhood cancer survivors, yet many have low activity levels. Using the WHO's International Classification of Functioning, Disability, and Health for Children and Youths (ICF‐CY) as a conceptual framework, we aimed to identify perceived barriers and facilitators to PA in young survivors and their parents. Design/methods: We conducted individual, semi‐structured interviews with 63 survivors, aged 9–18 years, ≥1‐year off treatment, and 68 parents, recruited from three pediatric oncology departments in Norway and Denmark. Interviews were analyzed inductively using thematic analysis to identify barriers and facilitators to PA, which were mapped onto the ICF‐CY model components; body function/structures, activities, participation, and environmental and personal factors. Results: Two‐thirds of the survivors described how treatment‐related impairments of bodily functions (e.g., fatigue, physical weakness, reduced lung capacity) caused physical limitations, reducing opportunities to participate in PA, especially team sports and school physical education. This resulted in a perceived ability gap between survivors and peers, reducing motivation for PA. These PA barriers were moderated by environmental factors that facilitated or further hindered PA participation (family, peer, and school support). Similarily, personal factors also facilitated (acceptance, motivation, goal setting) or hindered (anxiety, low motivation, and lack of trust) PA participation. Conclusion: Treatment‐related long‐term or late effects represented significant barriers to PA as their functional consequences reduced survivors' capacities and capabilities to be active. Environmental and personal factors acting as facilitators or further barriers to PA were identified. Applying the ICF‐CY framework in clinical practice could help to enable PA participation.